APLIKASI TEKNIK EYESHADOW CUT CREASE DENGAN EYELID TAPE ATAU TANPA EYELIDE TAPE PADA BENTUK MATA MONOLID UNTUK TATA RIAS PENGANTIN BARAT - Anggraini, Rhavinda Dwi; Sri Dwiyanti; Nia Kusstianti; M.A. Hanny Ferry Fernanda (Jurnal Tata Rias, 2026)
In Western bridal makeup, understanding eye shape characteristics is fundamental for determining appropriate eye correction techniques. One commonly used method is the application of eyelid tape, particularly to help create an eyelid crease for monolid eyes. This study is intended to analyze the findings of monolid eye makeup using the eyeshadow cut crease technique with and without eyelid tape, as well as to identify and examine the differences between two techniques. The research was conducted using a quantitative methodology with an experimental design and involved 30 observers as evaluators. The independent variables were the eyeshadow cut crease technique with eyelide tape and without eyelide tape, while the dependen variable was the final makeup finding. Data analysis was conducted using mean score calculations. The results showed that the technique using eyelid tape achieved a score of 3.5 (very good), whereas the technique without eyelid tape scored 3.1 (good), with statistical testing indicating a significant difference between the two. These findings confirm that the use of eyelid tape in the eyeshadow cut crease technique enhances the quality of monolid eye makeup in Western bridal makeup.